Manors and scattered farms: special settlement forms of outskirt areas in Hungary - Balogh, András; Csapó , Tamás (Journal for Geography, 2013)
The Hungarian settlement network is very varied and multiple. In the teeth of its small territory we can find many area-specific settlement forms in the country. These settlement forms are usually not independent municipalities, but mostly occupied the outer areas of some towns and villages. In this study we try to demonstrate two types of these special settlement forms: scattered farms and manors. Scattered farms are sporadic, lonely settlements of the Great Hungarian Plain, which are centres of agricultural works and generally the centres of economic activities now, but they used to serve as winter shelters for the livestock. Most of the manors could be found in Transdanubia. The leader utility is the agriculture, but among others we found manors with industrial, sanitary, tourism functions also.